Effects of the nitric acid concentrations on the etching process, structural and optical properties of porous zinc oxide thin films - C.G., Ching; Leonard, Lu; C.I., Ang; P.K., Ooi; S.S., Ng; Z., Hassan; H., Abu Hassan (Universiti Kebangsaan Malaysia, 2013)
The present study reports on the fabrication of porous zinc oxide by wet chemical etching. ZnO thin films were deposited via radio-frequency magnetron sputtering on p-type silicon with (111) preferred orientation. The etchants used in the present work were 0.1% and 1.0% nitric acid (HNO3) solutions. ZnO were etched at various times and were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and photoluminescence (PL) spectroscopy to allow the examination of their structural and optical properties. The XRD results revealed that the intensity of ZnO(002) decreased when the thin films were etched in varying HNO3 concentrations over different periods of time. The above observation is attributed to the dissolution of the ZnO(002). The SEM images showed that the thickness of the ZnO layers decreased over the etching time, which resulted from the isotropic etching by the HNO3 solution. The PL emission intensity initially increased with increasing etching time. However, with further etching of the samples, the PL spectra showed a decreasing trend in intensity as a result of the decrease in the surface-to-volume ratio. All results lead to the conclusion that 1.0% HNO3 has the capability to change the ZnO surface significantly.